Wet Chemical Treatment and Mg Doping of p-InP Surfaces for Ohmic Low-Resistive Metal Contacts - Ebrahimzadeh Masoud; Granroth Sari; Vuori Sami; Punkkinen Marko; Miettinen Mikko; Punkkinen Risto; Kuzmin Mikhail; Laukkanen Pekka; Lastusaari Mika; Kokko Kalevi (Wiley-VCH Verlag GmbH & Co. KGaA, 2025)
Manufacturing a low-resistive Ohmic metal contact on p-type InP crystals for various applications is a challenge because of the Fermi-level pinning via surface defects and the diffusion of p-type doping atoms in InP. Development of wet-chemistry treatments and nanoscale control of p-doping for InP surfaces is crucial for decreasing the device resistivity losses and durability problems. Herein, a proper combination of HCl-based solution immersion, which directly provides an unusual wet chemical-induced InP(100)c(2x2) atomic structure, and low-temperature Mg-surface doping of the cleaned InP before Ni-film deposition is demonstrated to decrease the contact resistivity of Ni/p-InP by the factor of 10 approximately as compared to the lowest reference value without Mg. Deposition of the Mg intermediate layer on p-InP and postheating of Mg/p-InP at 350 °C, both performed in ultrahigh-vacuum (UHV) chamber, lead to intermixing of Mg and InP elements according to X-ray photoelectron spectroscopy. Introducing a small oxygen gas background (O2~10-6 mbar) in UHV chamber during the postheating of Mg/p-InP enhances the indium outdiffusion and provides the lowest contact resistivity. Quantum mechanical simulations indicate that the presence of InP native oxide or/and metal indium alloy at the interface increases In diffusion